Dynamics of Oil and Fatty Acid in Historical Sorghum Varieties - N. S. Volpato; A. J. P. Carcedo; T. Durrett; L. Marziotte; L. Mayor; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2023)
One of the important characteristics of cereal crops is their diverse pool of fatty acids. This study aims to determine the changes in sorghum oil content and fatty acid profile across many years of the market’s variety releases. Six sorghum varieties, all released between 1960 and 2019, were evaluated and grain traits were analyzed using linear models. Ten different fatty acids were characterized, but only three out of the total represented more than 90% of the total oil concentration: linoleic, oleic, and palmitic acid. Total oil and linoleic acid concentration (g of oil/kg) slightly decreased across years of release. In contrast, palmitic and oleic acid concentrations (g of oil/kg) increased over time. These results indicate past breeding efforts have not substantially modified sorghum’s profile of fatty acids.
Keywords: linoleic acid; palmitic acid; oleic acid; Sorghum bicolor (L. Moench); genetic gain; seed quality